2014
DOI: 10.1177/0733464814530804
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Sense of Self by People With Alzheimer’s Disease in a Support Group Interpreted in Terms of Agency and Communion

Abstract: The self is constructed in cooperation with other people and social context influences how people perceive and express it. People with Alzheimer's disease (AD) often receive insufficient support in constructing their preferred selves, but little is known about how they express themselves together with other people with AD. In accordance with Harré's social constructionist theory of self, this study aimed to describe how five people with mild and moderate AD express their Self 2 (i.e., their personal attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 58 publications
(59 reference statements)
1
29
0
Order By: Relevance
“…Furthermore, there was evidence that patients used humor to assert themselves, for example to raise concerns (Robinson et al, 2010), manage difficult feelings and lighten serious discussions (Hedman et al, 2014a), claim control in assessments and group conversations (Saunders, 1998b;Hedman et al, 2014b), and hide miscomprehension and maintain interactional flow (Saunders, 1998b;Lindholm, 2008). These studies argued that by using humor flexibly to both dominate talk and be self-deprecating, patients are showing insight into their expected responses and limitations and demonstrating that they are "productive members of the interaction" (Saunders et al, 2011).…”
Section: P a T I E N T F A C E W O R K : C O M P E N S A T O R Y S T mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there was evidence that patients used humor to assert themselves, for example to raise concerns (Robinson et al, 2010), manage difficult feelings and lighten serious discussions (Hedman et al, 2014a), claim control in assessments and group conversations (Saunders, 1998b;Hedman et al, 2014b), and hide miscomprehension and maintain interactional flow (Saunders, 1998b;Lindholm, 2008). These studies argued that by using humor flexibly to both dominate talk and be self-deprecating, patients are showing insight into their expected responses and limitations and demonstrating that they are "productive members of the interaction" (Saunders et al, 2011).…”
Section: P a T I E N T F A C E W O R K : C O M P E N S A T O R Y S T mentioning
confidence: 99%
“…There were several studies that evidenced the assistance that patients give each other to maintain face in support groups (Mason et al, 2005;Hedman et al, 2014aHedman et al, , 2014b or day center group interactions (Lindholm, 2013). Lindholm found that group members would compensate for others' difficulties, for example by slowing down their talk and repeating turns.…”
Section: P a T I E N T F A C E W O R K : C O M P E N S A T O R Y S T mentioning
confidence: 99%
“…Table 1 provides details about the studies evaluating support group outcomes, Table 2 lists the outcome findings from these studies and the processes, such as reflection or mutual support that occurred within groups. Publications spanned 25 years: the first paper reported a time-limited group with psycho-education components (McAfee et al, 1989), whilst recent publications referred to an open-ended group with no additional components (Hedman et al, 2014a;2014b). Papers referring to open-ended Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Caregivers could also attend the support group but groups that did not include the person with dementia were excluded, therefore caregiver support groups were not included. How authors defined their group was noted but due to the variable use of the term "support group" (Hedman et al, 2014a) all interventions were critiqued against the definition of a support group developed for the review. For the review, support groups were defined as:…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation